Effects of adding vertical or horizontal force-vector exercises to in-season general strength training on jumping and sprinting performance of youth football players - Abade, E.; Silva, N.; Ferreira, R.; Baptista, J.; Gonçalves, B.; Osório, S.; Viana, J. (The Journal of Strength and Conditioning Research, 2021)
Football is characterized by short-term high-intensity triaxial activities that require optimized neuromuscular capacity. Thus, training routines must consider the direction of force application, particularly when strength exercises are performed. This study aimed to explore the effects of adding vertical or horizontal force-vector exercises to a 20-week in-season general strength training program on jumping and sprinting performance of youth football players. Twenty-four well-trained male under-17 players participated in this study and were randomly assigned to a control, vertical, or horizontal training group. Control group performed a general strength training program (free weights, eccentric-overload, and body mass exercises) once a week during 20 weeks. Vertical and horizontal groups additionally performed back-half-squat or barbell hip-thrust, respectively. Vertical group improved vertical jump (VJ) (squat jump, likely 4.5; ±4.4% and countermovement jump, likely 4.9; ±4.1%), horizontal jump (HJ) (most likely 7.5; ±2.7%), and sprint (10 m, likely -1.6; ±2.0% and 20 m, very likely -3.3; ±1.6%). The horizontal group showed unclear results in VJ; however, large improvements were observed in HJ (most likely, 13.0; ±4.8%), 10 m and 20 m (very likely -3.0; ±1.8% and most likely -3.8; ±1.0%, respectively). Back-squat and hip-thrust showed an important transference effect to both jumping and sprinting performance. If considering the effects of back-squat on VJ, hip-thrust improved HJ and sprint to a greater extent. This study reinforces the importance of performing both vertical and horizontal force-vector exercises to enhance physical performance during football in-season, even when performed only once a week.